(untitled) (diségno, 2026)
Between 1922 and 1926, Hugo Häring designed and built part of the Gut Garkau agricultural complex, located on the southern shore of Lake Pönitzer See. This work is a clear example of functionalist expressionism with vernacular influences, inspired by ideas of Hans Poelzig and later developed by Bruno Taut and Erich Mendelsohn. Häring claimed that the form of the building should come from its function, without imposing preconceived forms, similar to how a living organism functions. When designing the farm, he analyzed in detail the agricultural culture, including daily tasks, the movement of animals and the distribution of industrial machinery, adapting the architecture to these needs. Its architectural expression responds to functional demands, using materials and structures that dialogued with the natural environment. From his project, the barn, stable and an annex building were built around 1924, while other proposals for the horse stable and pigsty remained on paper. The barn, the most prominent part, features an arched roof in the form of a light vault, with a wooden structure formed by a three-dimensional mesh of diamonds, based on the Zollinger system. The study seeks to show how Häring achieved a clear formal expression that reflects the function for which the building was conceived.